Identification of Channeling in Pore‐Scale Flows. Issue 6 (29th March 2019) - Siena, Martina; Iliev, Oleg; Prill, Torben; Riva, Monica; Guadagnini, Alberto
Abstract: We quantify flow channeling at the microscale in three‐dimensional porous media. The study is motivated by the recognition that heterogeneity and connectivity of porous media are key drivers of channeling. While efforts in the characterization of this phenomenon mostly address processes at the continuum scale, it is recognized that pore‐scale preferential flow may affect the behavior at larger scales. We consider synthetically generated pore structures and rely on geometrical/topological features of subregions of the pore space where clusters of velocity outliers are found. We relate quantitatively the size of such fast channels, formed by pore bodies and pore throats, to key indicators of preferential flow and anomalous transport. Pore‐space spatial correlation provides information beyond just pore size distribution and drives the occurrence of these velocity structures. The latter occupy a larger fraction of the pore‐space volume in pore throats than in pore bodies and shrink with increasing flow Reynolds number. Plain Language Summary: The movement of fluids and dissolved chemicals through porous media is massively affected by the heterogeneous nature of these systems. The presence of "fast channels, " that is, preferential flow paths characterized by large velocities persisting over long distances, gives rise to very short solute travel times, with key implications in, for example, environmental risk assessment. While efforts in the characterization of this phenomenon mostly address processes at the continuum (laboratory or field) scale, it is recognized that pore‐scale channeling of flow may affect the system behavior at larger scales. Here we provide criteria for the identification of fast channels at the pore scale, addressing feedback between channeling and geometrical/topological features of the investigated porous structures. Our results clearly evidence the major role of well‐defined regions in the pore space, termed pore throats, in driving flow channeling. We also find that the strength of channeling is controlled by the characteristic Reynolds number of the flow field. Key Points: Fast channels in 3‐D pore‐scale flow fields are identified as connected regions of the pore space where velocity outliers are found The topology of the network of pore bodies and throats forming the pore space drives spatial distributions of fast channels Fast channel size decreases as the Reynolds number increases and is related to the strength of preferential flow and anomalous transport